Multiple Hereditary Exostosis of Distal Ulna with Dislocation of Radial Head: A Case Report - Utomo, Pamudji; Idulhaq, Mujaddid; Brilianto, Bagus Iman (Indonesian Journal of Medicine, 2020)
Background: Multiple hereditary exostosis of the forearm is typically formed in the distal ulna causing disturbances in the growth of the ulna and functional disability. Multiple hereditary exostosis inhibits the growth of the ulna leading to an acquisition of a varus deformity in the radius which sometimes leads to dislocation of the radial head, the development of limitations in the pronation-supination of the forearm, and cosmetic problems. This study aimed to report the multiple hereditary exostosis of distal ulna with dislocation of radial head.Case Presentation: We present a case of a 14 year-old girl with main complaint of a bony prominence on her right elbow which limits the elbow flexion range of motion. 3D CT-Scan revealed a dislocation of radial head, shortening and posterior bowing of ulna. We performed excision of the prominent radial head, reconstruction, and temporary arthrodesis of the elbow.Results: The forearm deformity in patients with multiple hereditary exostosis related to the cross-sectional area of the distal ulnar physis was only one-quarter of the distal radius, the distal ulna is more involved in the condition. There was more longitudinal growth at the distal ulnar physis than at the distal radial physis, the distal ulnar physis contributed more total Ulnar Length than the distal radial physis did to Radial length. Known surgical interventions including simple excision, ulnar lengthening, corrective radial osteotomy, hemi-epiphyseal stapling of the distal radius, the Sauve-Kapandji procedure.Conclusion: Simple excision could improve the range of movement of the forearm but would not halt the progression of disease, particularly in younger patients. It was not effective in controlling progression of the deformity. Mature patients did not recur, but in patients that had been excised before puberty the results were varied and unpredictable.Keywords: multiple hereditary exostosis, radial head dislocation, excisionCorrespondence: Pamudji Utomo. Department of Orthopaedics and Traumatology Prof. Dr. R.Soeharso Orthopaedics Hospital, Surakarta. Email: utomodr@yahoo.com.Indonesian Journal of Medicine (2020), 05(01): 63-69https://doi.org/10.26911/theijmed.2020.05.01.10